2023
DOI: 10.1021/acs.nanolett.3c01728
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Correlated Piezoelectricity in Quasi-Two-Dimensional Zinc Oxide Nanosheets

Abstract: Two-dimensional (2D) piezoelectric materials have recently drawn intense interest in studying the nanoscale electromechanical coupling phenomenon and device development. A critical knowledge gap exists to correlate the nanoscale piezoelectric property with the static strains often found in 2D materials. Here, we present a study of the out-of-plane piezoelectric property of nanometer-thick 2D ZnO-nanosheets (NS) in correlation to in-plane strains, using in situ via strain-correlated piezoresponse force microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…First, it can be an artifact, i.e., it can be caused by the AFM technique itself or by AFM equipment. Second, the piezoelectric coefficient (in the direct, atomistic meaning) can vary due to different mechanical stresses in the HZO on the membrane and on the rigid substrate . Third, the observed effect may be the nanoscopic electromechanical behavior of the predeformed piezoelectric nanomembrane, i.e., we may have observed the operation of a miniature piezo device.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…First, it can be an artifact, i.e., it can be caused by the AFM technique itself or by AFM equipment. Second, the piezoelectric coefficient (in the direct, atomistic meaning) can vary due to different mechanical stresses in the HZO on the membrane and on the rigid substrate . Third, the observed effect may be the nanoscopic electromechanical behavior of the predeformed piezoelectric nanomembrane, i.e., we may have observed the operation of a miniature piezo device.…”
Section: Resultsmentioning
confidence: 98%
“…Second, the piezoelectric coefficient (in the direct, atomistic meaning) can vary due to different mechanical stresses in the HZO on the membrane and on the rigid substrate. 16 Third, the observed effect may be the nanoscopic electromechanical behavior of the predeformed piezoelectric nanomembrane, i.e., we may have observed the operation of a miniature piezo device. Note that all of the above phenomena are related to the flexibility of the piezoelectric bridge membranes.…”
Section: Local Ferroelectric and Piezoelectric Propertiesmentioning
confidence: 93%
“…[42] Carlos et al measured the d 33 value of quasi-ZnO nanosheets between 2.1 and 20.3 pm V À1 . [43] It has been also reported that even number-layered MoS 2 does not exhibit piezoelectricity due to the centrosymmetrical nature, whereas the odd number layers of the sample exhibited a piezoelectric phenomenon due to noncentrosymmetric nature as the symmetry of MoS 2 layers is broken via applying external mechanical stress. Our present finding also suggests that the as-grown Li-doped MoS 2 nanosheets has an odd number of layers.…”
Section: High-resolution Transmission Electron Microscope Of Li-doped...mentioning
confidence: 96%
“…Nanoscale electronic device systems and energy harvesting applications are promising for two-dimensional (2D) layered materials. In recent years, interest in 2D materials made of piezoelectric, flexoelectric, triboelectric, and hybrid system has increased. , For emerging wearable electronics technologies, 2D materials are widely used due to their weak interlayer contacts, van der Waals (vdW) interactions, easily connected with the external surface, and high flexibility. In fact, 2D material/soft matter interfaces have been used in the transfer, printing, and processing of various electronic technologies. These interfaces are crucial for controlling the structural and morphological aspects, adjusting the physical properties, and enhancing the functionality of flexible devices made of soft substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, interest in 2D materials made of piezoelectric, flexoelectric, triboelectric, and hybrid system has increased. 12,13 For emerging wearable electronics technologies, 2D materials are widely used due to their weak interlayer contacts, van der Waals (vdW) interactions, easily connected with the external surface, and high flexibility. 14−18 In fact, 2D material/soft matter interfaces have been used in the transfer, printing, and processing of various electronic technologies.…”
Section: Introductionmentioning
confidence: 99%